2021
DOI: 10.1016/j.tmp.2021.100862
|View full text |Cite
|
Sign up to set email alerts
|

Smart governance for heritage tourism destinations: Contextual factors and destination management organization perspectives

Abstract: The sustainable development of tourism is a major concern for destination management organisations (DMOs) in heritage tourism. Smart tourism advocates claim that technologicallydriven innovations can help DMOs to optimise tourism development by addressing issues such as carrying capacity, stakeholder management and community involvement. This study enhances the understanding of smart tourism governance (SG), showing how contextual factors affect DMO perspectives of SG. A mixed-methods approach was used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 122 publications
1
24
0
4
Order By: Relevance
“…An equitable context of investigation is environmental planning and management, with particular regard to the design and assessment of projects inspired by Nature-Based Solution approach (NBS) (Quagliolo et al 2023). Last, but not least, the context of sustainable tourism planning could trigger interesting insights in terms of design of circular policies and actions, since projects and interventions developed in tourism destinations impact strongly on the environment, where local communities consensus could not be always reached (Cimnaghi and Mussini 2015;Mandić and Kennell 2021).…”
Section: Integrated Evaluation Framework: a Methodological Proposalmentioning
confidence: 99%
“…An equitable context of investigation is environmental planning and management, with particular regard to the design and assessment of projects inspired by Nature-Based Solution approach (NBS) (Quagliolo et al 2023). Last, but not least, the context of sustainable tourism planning could trigger interesting insights in terms of design of circular policies and actions, since projects and interventions developed in tourism destinations impact strongly on the environment, where local communities consensus could not be always reached (Cimnaghi and Mussini 2015;Mandić and Kennell 2021).…”
Section: Integrated Evaluation Framework: a Methodological Proposalmentioning
confidence: 99%
“…The idea about smart city served as the inspiration for the first smart tourism destination (Bulchand-gidumal, 2022;Gelter et al, 2022bGelter et al, , 2022aMandi & Kennell, 2021b). A "smart city" is one that can increase its residents' quality of life while also becoming more competitive (Borghys, 2020).…”
Section: Literature Review Smart Tourism Destinations (Std)mentioning
confidence: 99%
“…Recently, developed Asian countries such as China, Taiwan, and South Korea are very enthusiastic about implementing smart tourism to increase the selling value industry of tourism (García-milon, Juaneda-ayensa, Olarte-pascual, & Pelegrín-borondo, 2020). The implementation of Smart Tourism has made a lot of progress to develop tourism that is oriented towards business information technology (Luo & Zhou, 2021;Mandi & Kennell, 2021a). Based on research (Gelter, Fuchs, & Lexhagen, 2022a), explains that it has found better developments in STD technology than others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di erent regions of rural tourism with a characteristic cultural background need to have a reasonable management model. From the deep level of the local cultural background, a reasonable strategic plan for rural tourism is formulated, together with computer-aided technology, to form a closed-loop system for rural tourism management [3][4][5].…”
Section: Introductionmentioning
confidence: 99%